Pendampingan Penguatan Karakter Pemuda “Muda Berkarakter, Hebat Berprestasi” - A Taufiq (ABDI KARYA : Pengabdian Kepada Masyarakat, 2025)
Strengthening character for young people plays an important role, especially in improving a person's individuality by increasing the analysis of one's strengths and weaknesses in facing or preparing oneself for the world of work or entering society, character is also a strong foundation if one's motivation is down, by strengthening one's character one can also manage yourself to be ready to compete under any circumstances. This assistance is carried out in the form of an approach, assistance and reinforcement to participants about the importance of strengthening character, such as the government's goal of preparing a better generation for a Golden Indonesia in 2045.